2021
DOI: 10.1093/jmammal/gyab068
|View full text |Cite
|
Sign up to set email alerts
|

Home range variation in leopards living across the human density gradient

Abstract: Home range size is a fundamental measure of animal space use, providing insight into habitat quality, animal density, and social organization. Human impacts increasingly are affecting wildlife, especially among wide-ranging species that encounter anthropogenic disturbance. Leopards (Panthera pardus) provide a useful model for studying this relationship because leopards coexist with people at high and low human densities and are sensitive to human disturbance. To compare leopard home range size across a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…With regard to intraspecific patterns in HR size, female HR size was a chief driver of HR selection for males. Previous local studies support this finding, asserting the importance of female HRs for male leopards (Bailey, 2005;Snider et al, 2021) and felids in general (Macdonald & Loveridge, 2010;Hunter, 2015). The ratio of male:female HR size was relatively stable over the global range (Appendix S3, Fig.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…With regard to intraspecific patterns in HR size, female HR size was a chief driver of HR selection for males. Previous local studies support this finding, asserting the importance of female HRs for male leopards (Bailey, 2005;Snider et al, 2021) and felids in general (Macdonald & Loveridge, 2010;Hunter, 2015). The ratio of male:female HR size was relatively stable over the global range (Appendix S3, Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Due to inconsistent prey availability under these harsh environmental conditions, foraging leopards likely require broader and larger movements. Previous research on leopards and other medium and large felids, such as the Eurasian lynx (Lynx lynx) in Europe, identified the importance of vegetation productivity on HR size (Herfindal et al, 2005;Snider et al, 2021), suggesting that this could be a general pattern among widely distributed felids (see also Nilsen et al, 2005). Thus, global warming might have (9) indicates the predictor was not part of that modelling procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, territorial animals are expected to defend a home range large enough to meet their needs, but no larger (Calsbeek & Sinervo, 2002). For both territorial and non‐territorial species, one key extrinsic determinant of home range size is forage resource availability, with home range size decreasing in more productive environments (Kodric‐Brown & Brown, 1978; Snider et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…leopard's average home range size of approx. 50 km 2 ) [ 39 ]. Studies have shown that large prey species were the most preferred prey of tigers, leopards and dholes, accounting for a significant portion of the total prey biomass [ 33 , 40 42 ].…”
Section: Methodsmentioning
confidence: 99%